Cowpea (Vigna unguiculata L. Walp) as ingredient in growing-fattening rations of improved guinea pigs (Cavia porcellus) - Choez A., Katherine (2018)
The objective of the study was to determine the productive and economic response of improved guinea pigs (Peru type I) fed with rations containing different levels of cowpea (Vigna unguiculata L. Walp). The study was conducted in a family farm of Lambayeque, Peru, using 40 weaned male guinea pigs of 15 days and 387.5 g of initial weight, under a completely randomized design. The guinea pigs were distributed in four treatments: T0, T1, T2 and T3 with 0, 10, 20 and 30% of cowpea in the rations, respectively. The concentrate was offered ad libitum, plus 150 g of alfalfa per animal/day. After seven weeks, bodyweight gain ranged from 10.3 to 12.0 g/day, concentrate consumption varied between 38.8 and 47.2 g/animal/day and carcass yield ranged between 65.0 and 66.6%, without significant differences between treatments. The best feed conversion of the concentrate was observed at T2 (3.6). The best economic merit was also in T2, which presented 20.7% extra income than T0. In conclusion, cowpea at the level of 20% in the growing-fattening rations of improved guinea pigs improves the rate of feed conversion and economic merit.